Pengaruh Model Pembelajaran Problem-Based Learning Berbantuan Aplikasi Kahoot terhadap Hasil Belajar Siswa Kelas X SMA - Stefania Sonia Manek; Ivony Sarlin Asa (Pusat Riset dan Inovasi Nasional, 2025)
This research aims to test whether the use of the problem based learning model assisted by the Kahoot application has an effect on the learning outcomes of class X students. The research sample consisted of 50 students in classes X A and X B using Shapiro Wilk. This research uses quantitative methods with a Quasi Experimental Design and a Nonequivalent Pretest-Posttest control group design scheme. Data was collected through pretest and posttest to obtain the N-Gain Score value between the experimental class and the control class. with a sampling technique using a purposive sampling method. Data analysis was carried out using parametric statistical tests, namely the independent sample t-test. Data analysis results Based on the results of data analysis obtained during the research, it shows that the N-gain score for the experimental class got an average score of 79.99 (80%) which was categorized as effective in using the problem based learning model assisted by the Kahoot application, while the control class got an average score of 15.13 (16%) which was categorized as ineffective in using conventional learning (lectures, discussions and questions and answers). When the hypothesis test was carried out using the independent sample t-test, Sig was obtained. (2-tailed) 0.000 ≤ 0.05 so there is a significant difference between the experimental class and the control class. Thus Ho is rejected and Ha is accepted. So it can be concluded that there is a significant influence of the PBL model assisted by the Kahoot application in geography subjects on the learning outcomes of class X SMA Sinar Pancasila students.